Suspected Johne's disease in a herd of dairy cattle: a case report - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Yee, Jia Yin; Osman, Abdinasir Yusuf; Haron, Abd Wahid; Saharee, Abdul Aziz (International Organization of Scientific Research, 2013)
Four adult Friesian cross cows were experiencing intermittent diarrhea and chronic weight loss in a dairy farm in Dengkil, Negeri Sembilan. They were managed semi-intensively with pelleted diet and kept with a herd of 80 dairy cattles. One of the cattle, Kuning, experienced drop in milk yield from 10L/day to 2L/day. Physical examination revealed a poor body condition score of 2/5 in all 4 cattles, although they have good appetite. The differential diagnoses were Johne's disease, fascioliasis, chronic salmonellosis and coccidiosis. Laboratory diagnosis of Ziehl- Neelsen stained faecal smears from all 4 cattles revealed presence of acid fast bacteria. Haematology and serum biochemistry results of all 4 cattles shown lymphocytosis and hyperglobulinemia. Based on the compatible clinical signs, haematology and serum biochemistry results, presence of acid fast bacteria, diagnosis of suspected Johne's disease is made. A herd screening revealed 9 out of 30 cattles had acid fast stained bacteria in the faeces.